Blade : Trinity [videorecording (DVD)] - Goyer, David S.; Snipes, Wesley; Kristofferson, Kris; Purcell, Dominic, 1970-; Biel, Jessica, 1982-; Reynolds, Ryan; Posey, Parker, 1968- (New Line platinum series., 2004)
A group of vampires resurrect "Drake" the all-powerful Count Dracula. Teaming up with the Nightstalkers, a group of similar-minded hunters, Blade is ready for battle. A scientist creates a potion that can kill Drake and the entire bloodsucking race.